Can the Inspection of Education face new challenges with its current approach? - Galicia Mangas, Francisco Javier (Avances en Supervisión Educativa, 2016)
This communication intends to value whether Inspection of Education could face some social and educational challenges from its current approach. For that purpose, we are going to start from the study of the present situation of the institution and some basic challenges such as improving coexistence and the progress of the quality of education through assessment, advice and coordination, trying to give at the same time a proposed action or work which contribute to accomplish these achievements or goals.